Konteksti snemanja govorjenega diskurza v sociolingvistiki: Maja Bitenc - Krajnc Ivič, Mira (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Contexts of Recording Speech in Sociolinguistics. The paper focuses on the contexts in which spoken language is collected and recorded, primarily from a sociolinguistic perspective. It provides an overview of methodological approaches in various foreign language and Slovene studies that analyse speech variation both at the level of the individual speaker and within speech communities. It presents William Labov's pioneering sociolinguistic interviews in the United States, which include different speech styles as well as methods for eliciting and analysing spoken discourse in more recent research projects in language communities with sociolinguistic profiles closer to Slovene, such as Austria, Germany, Belgium and Hungary. These include activities such as reading texts and word lists, translation from dialect to standard and vice versa, informal conversations with friends from the same and different dialect areas, formal sociolinguistic interviews with researchers, recordings of friendly conversations, recordings for other purposes and participant observation. The existing studies on language variation in Slovene, which record speech in various more or less authentic everyday situations, are also analysed.